Characterization of cultivars and low-temperature pollen grain storage in amaryllis (Hippeastrum sp.) - Naiara Vallado de Almeida; Camila Y. Nishimura Saziki; Jean Carlos Cardoso (Revista Ceres, 2019)
ABSTRACT The determination of viability and the preservation of pollen grains are useful tools for breeding of ornamentals, especially when the synchronization of flowering between species or cultivars does not occur naturally. Thus, the objective of this study was to characterize the flowering and to evaluate the preservation and maintenance of the viability of pollen grains in cultivars of amaryllis (Hippeastrum sp.) subjected to three storage temperatures. Anthers of five cultivars of amaryllis were collected from 12 to 24 hours after anthesis. One part of the anthers was immediately used for germination tests using in vitro germination in culture medium and the other part was stored at temperatures of 25, 8 and -20 °C. Pollen grains were germinated in culture medium at 0, 20, 75, 125, 165, 205 and 245 days after storage. All cultivars of amaryllis showed an accelerated loss of viability at 25 °C storage temperature. The 'Bull' cultivar showed higher recalcitrance to cold-storage, while 'Intokazie' and 'Pink Panther' cultivars showed higher longevity and higher percentage of germination along storage. The temperature of -20 °C resulted in the best responses for the maintenance of the integrity and preservation of the viability of pollen grains of different cultivars of amaryllis.